STUDI PEMIKIRAN IBNU QUDAMAH TENTANG NIKAH BERSYARAT - Vevi Alfi Maghfiroh (MAHAKIM Journal of Islamic Family Law, 2019)
Marriage is the process by which two people make their relationship public, official, and permanent. It is the joining of two people in a bond that putatively lasts until death. Marriage is the foundation of the building, and its position is very important according to the Qur’an, based on the number of verses that talk about marriage relations. Before the wedding, sometimes there are conditions agreed upon by the bride and groom or from the bride’s parents whose purpose is for the good of them.The law to make marriage agreements (conditional marriage) is permissible (muba>h}). It may or may not be done, but if the agreement is done, then the law of its implementationwas debated by the scholars.Based on the background and data analysis obtained from the research findings mention that there are two groups who have different views about conditional marriage. They are Ibn Qudamah who is a H{anbali scholar and the majority of scholars (Jumhur ulama) which includes Ima>m Sya>fi’i, Ima>m Ma>lik. and Ima>m H{anafi. This problem of dissent needs to be examined, with the opinion of Ibn Qudamah as a scholar (pentarjih). He firmly argued that if the marriage conditions had been stated, the law must be implemented. It was viewed from the istidlal method then accordingto the argument of Al-Qur’an: Al-Maídah verse 1, Al-Isra verse 34, and An-Nah}l verses 91-92, Hadiṡ Uqbah bin Amir, Fatwa Sahabat that becomes an ijma ‘, also Qiyasbecause keeping promises is a demand ofsyara’